The Design of Decision Support System to Improve E-Learning Environments - VishnuPriya, S; Mary, M. P. Virgin (International Journal of Computer Sciences and Engineering, 2025)
E-Iearning is a new topic in education environments and gradually has found its proper place in the recent training methods. But due to the fact that, there is no face to face contact between the teachers and students in e-learning systems, neither the teachers nor the students in the course are aware of each other's behavior, so in these types of systems, the need of feedback between the students and the professors is felt , this will help improve the teaching and learning process. Although most of these systems can offer a reporting tool" the teachers, in general, cannot provide a clear view about the status of their students. In this paper we investigate efficient query search, as well as global issues, with the aim of solving this problem with a new approach in the design of decision support systems, a system which would enable teachers to answer questions like these in order to understand students' academic achievement using data mining techniques based on the data in the database management system for educational content. Finally, the paper concludes and suggests that teachers of these courses do not require the learning and data mining techniques, but only a model or models are needed to interpret the results of teachers and other educational activities that are essential to help